Excerpts from the research on the spatial layout of the Josephine villages in the area of former Galicia - Cepil, Monika (Przestrzenny wymiar badań dziedzictwa kulturowego: Studia z Geografii Politycznej i Historycznej 2020. T. 9-10, 2021)
The main aim of the chapter is to analyze the preserved forms of the Josephine villages in the area of former Galicia. After a short introduction concerning legal aspects of delimitation of new villages, the newly created forms of settlements were interpreted. The analyses covered the following forms: street-type villages (including streetplane) and multi-way (including concentric-radian, checkered lattice and cross-radian) villages. The next part of the chapter depicts the remains of former rural settlements of the Josephine villages against the background of the contemporary settlement network. The comparative analysis covers the processes of changes in small rural settlements on Polish and Ukrainian territory. Cartographic materials and source documents obtained during queries at the National Archive in Krakow, the State Archive in Przemyśl and the Central State Historical Archive of Ukraine in Lviv were used in the realization of the assumed research problem. The main source materials used in the chapter are: plans of the Josephine villages from the end of the 18th century, the Josephine Metric, the Franciscan Metric and the Galician Cadastre. In depicting the current state of preservation of the small rural settlements, publicly available topographic maps, aerial photographs and field inventory were used.